Automated safety cushion for high-rise building / Nasuha Mohamed Raza and Siti Akhtar Mahayuddin - Mohamed Raza, Nasuha; Mahayuddin, Siti Akhtar (2019)
The rapidly development of high-rise projects has leaded to the rise of fatalities and accidents. Most of the construction workers are frequently exposed to various types of injury such as falling from heights. As a result of uncertain and harmful nature, accidents on construction usually happen and cause lots of negative consequences, such as absenteeism and project delays. As a result, automated safety cushion is proposed to be applied in construction might significantly contribute to reduce the number of workers accidently falling from high. Safety cushion is used in emergency situations for rescue of people from high buildings. Safety cushion will absorb the shock of the fall with a comfortable and safe body response. With the help of technology, the automated safety cushion will be automatically function without human help. This paper aims to propose an innovation to reduce fall accident and to identify the significant of innovation to the problem. This innovation will help to prevent injury for the worker from falling from high and this will increase the worker safety at site.